Analysis of A Case of Growth Retardation of Infants Caused By Maternal Medication During Lactation - Zhang, Junhua (BIO web of conferences, 2024)
Short stature in childhood and even adulthood mostly originates from infancy and young children. It has been reported that 30.7% of children start to experience short stature before 6 months of age, 32.3% of children start to experience short stature between 6 and 24 months of age, and 88.3% of children start to experience short stature before 3 years of age [1]. In outpatient visits to children with short stature, the proportion of idiopathic short stature (ISS) is as high as 41% [2]. This article discusses and analyzes cases of commonly used drugs during postpartum lactation that may lead to delayed growth and development in infants and young children, aiming to identify the causes of growth retardation in this stage and improve prevention and intervention for growth retardation in infants and young children.